Addressing BBB Heterogeneity: A New Paradigm for Drug Delivery to Brain Tumors - Jessica I. Griffith; Sneha Rathi; Wenqiu Zhang; Wenjuan Zhang; Lester R. Drewes; Jann N. Sarkaria; William F. Elmquist (MDPI AG, 2020)
Effective treatments for brain tumors remain one of the most urgent and unmet needs in modern oncology. This is due not only to the presence of the neurovascular unit/blood-brain barrier (NVU/BBB) but also to the heterogeneity of barrier alteration in the case of brain tumors, which results in what is referred to as the blood-tumor barrier (BTB). Herein, we discuss this heterogeneity, how it contributes to the failure of novel pharmaceutical treatment strategies, and why a "whole brain" approach to the treatment of brain tumors might be beneficial. We discuss various methods by which these obstacles might be overcome and assess how these strategies are progressing in the clinic. We believe that by approaching brain tumor treatment from this perspective, a new paradigm for drug delivery to brain tumors might be established.